U.S. Military Children and the Wartime Deployments of Family Members. (13th November 2016) - MacDermid Wadsworth, Shelley; Bailey, Keisha M.; Coppola, Elizabeth C.
Abstract: In 2014, 1.8 million American children lived in military families, and they represented only a fraction of the U.S. children exposed directly to parents' wartime deployments over the past 15 years. In this article, we summarize recent research about military children in U.S. families and propose directions for research. Emerging from studies across the country are troubling elevations in levels of risky behaviors and mental health problems in military children, particularly when their parents have been deployed. The experiences of children in military families can help us understand risk and resilience not just in military children but in children in the general population.